Decoding Mafic Dykes in Southern Yilgarn and East Antarctica: Implications for the Supercontinent Cycle - Stark, Jutta (Curtin University, 2018)
This PhD study reports the discovery of three previously unknown mafic dyke swarms in the Yilgarn Craton in Western Australia and the first precise age for a mafic dyke swarm in East Antarctica. These ages fall in key periods of supercontinent cycle between the Neoarchean and the Mesoproterozoic, and make an important contribution to the global database of mafic dykes and Large Igneous Provinces.